Mapping wet vs gel spinning in Hansen space. (16th September 2021) - Jimenez, Javier; Ford, Ericka
Abstract: The composition of coagulation baths for solution spun fibers are typically established through trial and error. No method currently exists to quantifiably differentiate wet from gel fiber spinning. Hansen Solubility Parameters (HSPs) characterize materials using a 3-dimensional coordinate system for dispersive ( δ D ), dipole-dipole ( δ P ), and hydrogen bonding ( δ H ) forces. This coordinate system was used to quantify the affinity of coagulation baths with respect to the polymer in the spinning solution. A correlation based on radial energy distribution (RED) was seen to consistently differentiate wet from gel spinning. If the HSP distance between the coagulation bath and polymer (Ra) is less than or equal to the inherent interaction radius (Ro ) of the polymer (RED ≤ 1), coagulant diffusion inward is observed, which is critical for wet spinning. If Ra is greater than Ro (RED > 1), negligible amounts of coagulant diffusion inward is observed, which is critical for gel spinning. This quantitative approach has applicability to a range of polymeric materials such as fiber, film, and membrane technologies. Graphical abstract: Image 1 Highlights: Coagulation can be quantified by Hansen Solubility Parameters. The relative energy difference (RED) differentiates wet from gel spinning. Wet spinning is associated with an RED ≤1 in Hansen space. Gel spinning is associated with an RED >1 in Hansen space.